Quality control implementation in aquaculture industries: Certification norms and procedures - Alava A. (Global quality assessment in Mediterranean aquaculture, 2000)
Navarra Food, S.A. (Spain) with an annual production of 2,500 t is one of the largest producers of trout in Europe. Frozen trout exports account for 95 per cent of sales. The evolution of the firm has involved both production and quality systems in order to meet internal and external requirements (customers, legislation, etc.). The firm's primary quality program was essentially based on end product testing, carrying out microbiological and sensorial analysis. With the publication of the R.D. 1437-1992 settling the sanitary norms to be applied in production and commercialisation of seafood and aquaculture products the company started to implement the HACCP system. The company met a series of difficulties, mainly related to documentation. On the other hand this system only covered prevention and detection of problems relating to food safety. In 1997 the company decided to implement a Quality Management System according to ISO 9002, which integrates HACCP.
Workshop of the CIHEAM Networks on Technology of Aquaculture in the Mediterranean (TECAM) and Socio-Economic and Legal aspects of Aquaculture in the Mediterranean, 1999/11/29-1999/12/01, Barcelona (Spain)